Singgah Sahur UMP for off-campus students and agencies - Nor Salwana, Mohammad Idris (UMPSA, 2023)
KUANTAN, 8 March 2023 - Universiti Malaysia Pahang (UMP) recently organised a Singgah Sahur programme involving off-campus student rental houses and several government agencies around Kuantan.